2015
DOI: 10.1109/tcpmt.2015.2453407
|View full text |Cite
|
Sign up to set email alerts
|

Integration of a 140 GHz Packaged LTCC Grid Array Antenna With an InP Detector

Abstract: Integration of a 140-GHz packaged lowtemperature cofired ceramic (LTCC) antenna with a power detector is demonstrated under the concept of antenna-inpackage. The detector is designed on an indium phosphide (InP) process. A grid array antenna in LTCC is designed to provide package for the detector. Coplanar ground-signal-ground (GSG) bond wires are used to connect the detector and the antenna. Parallel plate mode is observed in the InP substrate and absorbed by the LTCC substrate. The comparison between the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 17 publications
1
28
0
Order By: Relevance
“…The demand for massive data transfer has driven the rapid development of high data rate wireless communication systems in the above-100 GHz mmWave bands or sub-terahertz ranges, such as the D band (110 -170 GHz), 270 GHz band, and 300 GHz band, in which the large bandwidth can be easily achieved. Recently, researchers have shown many high data rate wireless systems above 100 GHz employing LTCC AiP designs [12,[39][40][41]. For example, a 300 GHz step-profiled horn antenna realized in 27 LTCC layers achieved a high gain of around 18 dBi over 72 GHz bandwidth [12].…”
Section: (1) 5g Aipmentioning
confidence: 99%
“…The demand for massive data transfer has driven the rapid development of high data rate wireless communication systems in the above-100 GHz mmWave bands or sub-terahertz ranges, such as the D band (110 -170 GHz), 270 GHz band, and 300 GHz band, in which the large bandwidth can be easily achieved. Recently, researchers have shown many high data rate wireless systems above 100 GHz employing LTCC AiP designs [12,[39][40][41]. For example, a 300 GHz step-profiled horn antenna realized in 27 LTCC layers achieved a high gain of around 18 dBi over 72 GHz bandwidth [12].…”
Section: (1) 5g Aipmentioning
confidence: 99%
“…In recent years, a few papers have described LTCC antennas and array antennas operating in the frequency range above 100 GHz [1][2][3][4][5]. However, most of the presented approaches are complicated, especially through the use of many vias, which greatly increase the manufacturing cost.…”
Section: Introductionmentioning
confidence: 99%
“…In order to decrease the effect of higher VSWR level, an irregular distance between neighboring radiators has been proposed [7], [8]. Also, this antenna consists of only two LTCC layers which is a very low cost solution in comparison to antennas documented in the literature [1][2][3][4][5]. Moreover, in this type of antenna radiating structure, special vias are not required to ensure proper antenna signal excitation.…”
Section: Introductionmentioning
confidence: 99%
“…At the moment, the D-band frequency range 141 to 148 GHz is proposed for back-haul point-to-point relay stations and thus, several D-band Grid Array Antennas (GAA) have been developed and characterized for this purpose lately [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In some cases Liquid Cristal Polymer (LCP) is used [1] and in some cases Low temperature Co-fired Ceramics (LTCC) [2][3][4][5][6]. A cost benchmark on these two antennas has shown that, in small volume production, counting volumes of 500 antennas, the two solutions are very similar in cost.…”
Section: Introductionmentioning
confidence: 99%